Prevalence of Insomnia among Post Covid 19 Elderly Population - Annie Jerin Retna, Raj; Kumaresan, Abathsagayam; Surya, Vishnuram; Prathap, Suganthirababu; Vignesh, Srinivasan; Vinodhkumar, Ramalingam; Preethi, Gokulan (INTI International University, 2023)
Introduction: Insomnia is defined as a persistent difficulty initiating or maintaining sleep, or by non-restorative sleep that causes daytime distress. Insomnia can lead to mental health issues such as depression and anxiousness, as well as an elevated risk long-term diseases or conditions like high blood pressure and heart disease. COVID -19 is a significant psychological stressor for patients. Patients are vulnerable to a variety of mental health issues even after they have recovered. Aim and objectives: The aim and objective of the study is to find out the prevalence of insomnia among post COVID- 19 elderly population. Methodology: This study is a survey. The study was conducted among 300 participants of post COVID 19 Elderly population. Based upon the inclusion and exclusion criteria participants were selected. The detailed procedure was explained to the participants and a written informed consent form was obtained. The insomnia severity Index scale was circulated among the participants and the obtained data was analyzed. Result: The values were statistically analyzed. This statistical analysis shows that in 1st wave 97 males and 73 females were affected and in 2nd wave 49 males and 71 females were affected. Conclusion: This article concluded that there is prevalence of insomnia among post COVID 19 elderly population.